1980
DOI: 10.1159/000181971
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestinal Dipeptidases and Disaccharidases in Experimental Uremia in Rats

Abstract: Rats were made severely uremic with partial nephrectomy (24-hour creatinine clearance 10% of normal). Jejunal dipeptidase activities (substrates: glycyl-L-leucine, L-alanyl-L-proline, and L-methionyl-L-methionine), disaccharidase activities (maltase, sucrase, trehalase, and lactase) and morphology were studied. A highly significant increase in glycyl-L-leucine and L-methionyl-L-methionine dipeptidases was found in uremic rats compared with controls. Proline dipeptidase activities were unaltered. Disaccharidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…We found that glycyl-L-leucine and L-methionyl-L-methionine dipeptidase activities were increased, but that the L-alanyl-L-proline dipeptidase activity was un changed in uraemic rats given a normal diet (24% protein) [1]. Our results presented in this paper indicate that glycyl-L-leucine and L-methionyl-L-methionine dipeptidase ac tivities decrease when low (6%) protein feeding is insti tuted, whereas the L-alanyl-L-proline dipeptidase activity increases.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…We found that glycyl-L-leucine and L-methionyl-L-methionine dipeptidase activities were increased, but that the L-alanyl-L-proline dipeptidase activity was un changed in uraemic rats given a normal diet (24% protein) [1]. Our results presented in this paper indicate that glycyl-L-leucine and L-methionyl-L-methionine dipeptidase ac tivities decrease when low (6%) protein feeding is insti tuted, whereas the L-alanyl-L-proline dipeptidase activity increases.…”
Section: Discussionmentioning
confidence: 81%
“…Uraemic rats given a diet with normal protein content exhibit increased activities of some dipeptidases in homo genate of mucosa and in brush border preparations [1,[17][18][19]. We found that glycyl-L-leucine and L-methionyl-L-methionine dipeptidase activities were increased, but that the L-alanyl-L-proline dipeptidase activity was un changed in uraemic rats given a normal diet (24% protein) [1].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Grimmer et al [5,6] showed a drecrease of sucrase and maltase activities of the intestinal mucosa, whereas Wizemann et al [19] found an increase of maltase and no change in lactase and sucrase, and Sterner et al [18] observed a slight increase of sucrase and no change in maltase, trehalase and lactase.…”
Section: Discussionmentioning
confidence: 99%
“…Although morphological dis orders of the gastrointestinal tract in chronic renal failure are well documented [1,3,8,9], conflicting data have been reported concerning intestinal enzyme activities [3,5,6,9,18,19],…”
mentioning
confidence: 99%